Intrinsic Kinetic Modeling with Explicit Radiation Absorption Effects of the Photocatalytic Oxidation of Cyanide with TiO2 and Silica-Supported TiO2 Suspensions - Marugan, Javier (2008)
This study is focused on the kineticmodeling of the photocatalytic oxidation of cyanide in slurry reactors. The developed model is based on an accepted reaction mechanism and explicitly takes into account the differences in the local volumetric rate of photon absorption (LVRPA) produced by the unavoidable radiation profiles existing in the photoreactor. The model and its correspondent procedures for the evaluation of the LVRPA distribution, and the estimation of the kinetic parameters have been successfully validated with both powder TiO2 and TiO2/SiO2 photocatalysts with improved recovery properties. In both cases, the model reproduces the influence of the catalyst loading, the initial cyanide concentration, and the inlet radiation flux on the reaction rate, with errors below 5%. The kinetic parameters estimated for the model are independent of the irradiation form, as well as the reactor size and its geometrical configuration, providing the necessary information for scaling-up and designing commercial scale photoreactors.